Morphological characteristics of the triathlete according to sex, category and competitive level - Canda, A. S.; Castiblanco, L. A.; Toro, A. N.; Amestoy, J. A.; Higueras, S. (Apunts Medicina de l'Esport, 2014)
The triathlon combines three resistance sport disciplines and requires physical characteristics to optimize the performance of each segment. The aim of this study was to determine the morphological profile of the triathlete. A retrospective analysis was performed on 153 protocols including: weight, height, perimeters, diameters, lengths, and skinfolds. The male and female samples were divided into senior and junior, and senior into first and second ranking levels.